Delayed-Onset Cranial Nerve Palsy After Transvenous Embolization of Indirect Carotid Cavernous Fistulas. Issue 4 (December 2021) - Wang, Arthur; Halbach, Van V.; Dowd, Christopher F.; Alexander, Matthew D.; Hallam, Danial K.; Ghodke, Basavarj; Moazami, Golnaz; Mandigo, Grace K.; Lavine, Sean D.; Meyers, Philip M.
Abstract : Background: Carotid cavernous fistulas (CCF) often present with diplopia secondary to cranial nerve palsy (CNP). Immediate development of postoperative CNP has been described in the literature. This study described delayed-onset of CNP after complete and reconfirmed obliteration of the CCF and resolution of initial CNP. Methods: A retrospective analysis was performed on patients with indirect CCF between 1987 and 2006 at 4 academic endovascular centers. Details of the endovascular procedures, embolic agents used, and complications were studied. Partial or complete obliteration was determined. Immediate and delayed cranial nerve palsies were independently assessed. Results: A total of 267 patients with symptomatic indirect CCF underwent transvenous endovascular treatment. Four patients (1.5%) developed delayed abducens nerve (VI) palsy after complete resolution of presenting symptoms after embolization. Delayed presentation ranged between 3 and 13 months after complete resolution of initial double vision and cranial nerve palsies. Transvenous coil embolization through the inferior petrosal sinus was performed in all 4 affected patients. All had follow-up angiography confirming durable closure of their CCF. MRI did not show new mass lesions or abnormal soft tissue enhancement. In all 4 patients, their abducens nerve (VI) palsy remained. Conclusions: Delayed CNP can develop despite complete endovascular obliteration of the CCF. The cause of delayed CNP is not yet determined, but may represent fibrosis and ischemia. Long-term follow-up is needed even after complete neurological and radiological recovery is attained in the immediate perioperative period.